1992
DOI: 10.1203/00006450-199205000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Triphosphate and Adenosine Increase the Pulmonary Blood Flow to Postnatal Levels in Fetal Lambs

Abstract: ABSTRAa. We investigated the hypothesis that purine nucleotides may mediate the pulmonary vasodilation that occurs at birth in fetal lambs. We studied nine fetal lambs 3 d after placement of intravascular catheters, a flow transducer around the left pulmonary artery, and an inflatable vascular occluder around the ductus arteriosus. The pressure-flow relationship of left lung during a brief occlusion of the ductus arteriosus was studied as an index of pulmonary vascular resistance. We investigated the pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 11 publications
2
29
1
Order By: Relevance
“…The plasma levels of ATP increased during exposure of fetal lambs to oxygen, alone or accompanied by lung distension (15,18). Infusion of ATP and its metabolites into fetal pulmonary artery reproduced the pulmonary vasodilation that occurs at birth in fetal lambs (19). Inhibition of ATP synthesis (16) or receptors for ATP and its metabolite adenosine (15,18) attenuated the birth-related pulmonary vasodilation in fetal lambs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasma levels of ATP increased during exposure of fetal lambs to oxygen, alone or accompanied by lung distension (15,18). Infusion of ATP and its metabolites into fetal pulmonary artery reproduced the pulmonary vasodilation that occurs at birth in fetal lambs (19). Inhibition of ATP synthesis (16) or receptors for ATP and its metabolite adenosine (15,18) attenuated the birth-related pulmonary vasodilation in fetal lambs.…”
Section: Discussionmentioning
confidence: 99%
“…Control fetal lambs had blood gas tension measurements at the same time points. In addition, the fetal mean systemic and pulmonary arterial pressures were measured at the same time points with the appropriate pressure transducers (model PT 100, Grass Instruments) and physiograph (model 7D, Grass), as described previously (19). After 8 days of ductal constriction, the ewe was euthanized and laparotomy and hysterotomy incisions were quickly opened.…”
Section: Creation Of Pphn Model This Study Was Approved By the Animamentioning
confidence: 99%
“…Several studies in animal models of pulmonary hypertension demonstrated the beneficial effects of ATP infusion in this setting [811][812][813][814][815]. Pulmonary hypertension is a serious problem in children with congenital heart defects.…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
“…ATP and adenosine increase pulmonary blood flow in perinatal lamb via P1 and P2 receptors that are independent of prostacyclin synthesis (Konduri et al, 1992), later identified as A 2A and P2Y 1 receptors , and shown to act via NO . An increase in ATP release during oxygen exposure may contribute to birth-related pulmonary vasodilation in lambs (Konduri and Mattei, 2002).…”
Section: E Vasculaturementioning
confidence: 99%